Correction: Jules Verne et l’imaginaire arctique - Battail, Jean-François (Nordic Journal of Francophone Studies/Revue nordique des études francophones, 2020)
This article details a correction to the article: Jean-Francois, B. (2020). Jules Verne et l’imaginaire arctique. Nordic Journal of Francophone Studies/Revue Nordique Des Études Francophones, 3(1), 32–42. DOI: https://doi.org/10.16993/rnef.31. This article details a correction to the article: Jean-Francois, B. (2020). Jules Verne et l’imaginaire arctique. Nordic Journal of Francophone Studies/Revue Nordique Des Études Francophones, 3(1), 32–42. DOI: https://doi.org/10.16993/rnef.31.